1986
DOI: 10.1038/321620a0
|View full text |Cite
|
Sign up to set email alerts
|

Structure of DNase I at 2.0 Å resolution suggests a mechanism for binding to and cutting DNA

Abstract: Bovine pancreatic deoxyribonuclease I (DNase I), an endonuclease that degrades double-stranded DNA in a nonspecific but sequence-dependent manner, has been used as a biochemical tool in various reactions, in particular as a probe for the structure of chromatin and for the helical periodicity of DNA on the nucleosome and in solution. Limited digestion by DNase I, termed DNase I 'footprinting', is routinely used to detect protected regions in DNA-protein complexes. Recently, we have solved the three-dimensional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
227
0
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 341 publications
(238 citation statements)
references
References 24 publications
10
227
0
1
Order By: Relevance
“…These results are also in agreement with DNase I footprinting studies of pol III holoenzyme on DNA that showed protection of 27-30 bp at a primer terminus (43). DNase I is a rather large cleavage agent and generally overestimates binding sites by ϳ3-5 nucleotides (44).…”
Section: Discussionsupporting
confidence: 88%
“…These results are also in agreement with DNase I footprinting studies of pol III holoenzyme on DNA that showed protection of 27-30 bp at a primer terminus (43). DNase I is a rather large cleavage agent and generally overestimates binding sites by ϳ3-5 nucleotides (44).…”
Section: Discussionsupporting
confidence: 88%
“…was defined by the sequence alignment. Suck and Oefner (1986) proposed another catalytic mechanism of DNase I from the three-dimensional structure of DNase I and the binding of Ca2+-thymidine 3',5'-diphosphate at the active site; that is, Glu 78 accepts a proton from His 134, and His 134 in turn accepts a proton from a water molecule, which then, as a nucleophile, attacks the phosphorus. However, from the structure of the DNA octanucleotide-DNase I complex, they later suggested the alternative mechanism involving the two histidine residues H252 and HI34 (Suck et al, 1988).…”
Section: Conservation Of Functionally Important Residuesmentioning
confidence: 99%
“…It has strong structural specificity for the geometry of the minor groove, and gives staggered cuts on each strand by a 'double hit' mechanism (Suck and Oefner 1986). Because it is a large enzyme of 30 kDa, and may be glycosylated, DNaseI only cleaves the most accessible DNA regions.…”
Section: A Flausmentioning
confidence: 99%